Evaluation of Guided Bone Regeneration Using Xenograft/APRF Mixture in Atrophic Posterior Mandible (Clinical and Radiographic Study) - Richa, Ramy; Osman, Essam; Attia, Nahed; Arakji, Hani; Shokry, Mohamed (European Scientific Journal, ESJ, 2023)
Introduction: The rehabilitation of the posterior mandible with dental implants represents a hard challenge for clinicians today due to the lack of supporting bone. Different surgical techniques are currently being used to augment the posterior mandible, where GBR is considered the most commonly used. Materials and Methods: Fifteen patients were selected to treat mandibular alveolar ridge resorption with guided bone regeneration using a titanium-reinforced membrane and a filling mixture of xenograft bovine bone and PRF. The membrane was fixed using a Meisinger pin control kit and Profix 3mm microscrews. A PRF membrane was used to cover the Ti-d-ptfe. Results: Swelling, pain, and numbness were evaluated using the mixture of PRF/xenograft as well as PRF membranes. The results showed promising results in terms of primary wound healing, whereas a significant bone quantity with a mean bone volume of 5.78 ± 0.81 was reported after 6 months. The primary implant stability recorded high values and significantly increased at a period of 6 months post-insertion (p = 0.037). Conclusion: It could be concluded that the PFR/xenograft mixture can be promising when used with the titanium-reinforced d-ptfe membrane in 3D ridge reconstruction of the atrophic posterior mandible; moreover, using the PRF membrane to cover the TI-d-ptfe membrane could enhance soft tissue healing as well as prevent soft tissue dehiscence due to the concentration of growth factors that can be released during primary wound healing. The xenograft/PRf mixture can be consistently utilized for the creation of new bone in severely atrophic ridges if used in GBR. The high ISQ at primary implant placement and at a period of 6 months post-insertion, according to Osstell, can explain the successful application of this mixture in 3D bone augmentation of the atrophic posterior mandible.